Comparison between The Efficacy of Concurrent Chemo-Radiation with Gemcitabine Followed by Intracavitary Radiotherapy in Patients with Locally Advanced Cervical Carcinoma - Tania, Afroja Begum; Alam, Sarwar; Ghosh, Ashim Kumar; Quader, Rezwanul; Mahmud, Tasnim (Asian Journal of Health Research, 2024)
Introduction: Commonest threatening cancer in our Asian round is Cervical cancer. Currently, platinum-based concurrent chemo-radiation therapy is the standard of care for locally advanced cervical cancer but treatment results are disappointing, particularly for women with bulky tumors. To improve this result, several non-platinum-based agents with concurrent chemo-radiation have been evolved. Material and Methods: This was a quasi-experimental study, where 33 patients with untreated invasive squamous cell carcinoma of the cervix of stage IIB to stage IVA were enrolled in the study from the Radiation Oncology Department of Rajshahi Medical College Hospital from April 2019 to March 2020. Duration of the study was 2 years. All patients received 150 mg/m² of Gemcitabine weekly along with external beam radiation therapy (EBRT). EBRT dose was 50 Gy in 25 daily fractions followed by intracavitary radiotherapy (ICRT) of 21 Gy in 3 fractions. Results: The mean patient age was 45.4 years. Most patients were in stage IIB (59.1%) with moderately differentiated tumors (62.1%). After three months of treatment, 81.8% showed complete response, 12.1% partial response, and 6.1% disease progression. Grade 2 and 3 hematological toxicities were common, including anemia (60.6% grade 2; 24.2% grade 3) and neutropenia (24.2% grade 2; 6.1% grade 3). Other side effects included diarrhea (42.4%), proctitis (36.4%), skin toxicity (45.5%), mild renal toxicity (3%), and grade 2 cystitis (9.1%). Conclusion: Gemcitabine-based concurrent chemo-radiation is a potential alternative for patients contraindicated for Cisplatin. However, larger randomized studies are needed to confirm its safety and efficacy.